Biochemical characterisation of six novel monoamine oxidase inhibitors identified in tobacco smoke : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Health Sciences at Massey University, Wellington, New Zealand - Hong, Sa Weon (Massey University, 2023)
Background: Tobacco smoking is supposed to be the most difficult addiction to give up, and nicotine has been observed as the main addictive agent found in tobacco smoke. However, research is showing that nicotine alone does not account for tobacco dependence. One hypothesis is that monoamine oxidase (MAO) inhibition from non-nicotine compounds in tobacco smoke contributes to nicotine addiction. Six new MAO inhibitors in tobacco smoke have been identified before this PhD project. Overall research aim: The overall research aim for this project was to characterize these six novel monoamine oxidase (MAO) inhibitors identified in tobacco smoke and study their interaction with MAO A and B enzymes. Methods: First, non-nicotinic components of tobacco smoke were tested for MAO inhibitory activity, using the kynuramine assay and recombinant human MAO enzymes. Next, a centrifugation-ultrafiltration method and a time-dependent assay were used as the primary tests of reversibility of the phenolic compounds. Then, Lineweaver-Burke (LB) plots were prepared to understand the kinetics and mechanism of inhibition of recombinant human MAO enzymes by the polyunsaturated fatty acids (PUFAs). Finally, molecular docking and in silico studies using SwissADME and PreADMET web tools were performed. Results: Catechols and hydroquinone showed potent irreversible MAO A inhibition. Among these, 4-methylcatechol displayed the highest activity for MAO A with an IC₅₀ value of 0.267 μM after 1h preincubation. Two PUFAs, α-linolenic acid and linoleic acid displayed potent inhibitory effect for MAO A with IC₅₀ values of 15.74 and 23.8 μM, respectively. Kinetic analysis revealed that α-linolenic acid and linoleic acid are competitive inhibitors of MAO A and MAO B. Molecular docking studies suggest that ternary complexes [MAO B-linoleic acid₂ species (EII)] may be formed. Conclusions: This PhD project showed that six novel MAOIs in tobacco smoke inhibited human MAO A and MAO B isoenzymes. The catechols and hydroquinone are irreversible MAO inhibitors, suggesting they may play a role in contribution to the addictive effects of nicotine and the low incidence of Parkinson’s disease in smokers. In addition, α-linolenic acid and linoleic acid are found to be reversible MAO inhibitors, suggesting these PUFAs may play a role in the lower MAO levels or activity in smokers. Overall, these findings suggest that MAO inhibitors from tobacco smoke may have pharmaceutical possibilities, perhaps in smoking cessation, or in relief of anxiety or depression or in Parkinson's and Alzheimer disease.
Keywords: Tobacco smoke; Composition; Monoamine oxidase; Inhibitors; Nicotine addiction; 310101 Analytical biochemistry; 420605 Preventative health care